A thermoplastic elastomer POE open-cell foam material and preparation method thereof

By optimizing the component ratio and foaming process, and using composite foaming agents and fiber functional fillers, the problems of low open porosity, insufficient compression rebound rate and high shrinkage rate of POE foam materials have been solved, and high-performance, environmentally friendly POE open-cell foam materials have been achieved, expanding their application range.

CN120424436BActive Publication Date: 2025-09-12SHANGHAI GER ADVANCE MATERIAL SEC&TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510950406.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-10
Publication Date
2025-09-12
Estimated Expiration
2045-07-10

AI Technical Summary

Technical Problem

Existing POE foam materials have problems such as low open porosity, insufficient compression rebound rate, weak adsorption performance, high shrinkage rate and low production efficiency. In addition, traditional foaming methods are not environmentally friendly and cannot meet the high-performance material needs in multiple fields.

Method used

By adopting continuous extrusion physical foaming technology, optimizing the component ratio and foaming process, using composite foaming agents such as supercritical nitrogen and air, combined with fiber functional fillers and compatibilizers, a three-dimensional network structure is formed to improve the material's open porosity, adsorption performance and anti-shrinkage performance.

Benefits of technology

It achieves high open porosity, strong adsorption performance, low shrinkage and high compression rebound rate. The material has excellent performance and is suitable for applications in multiple fields, meeting the needs of green and low-carbon economic development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention discloses a thermoplastic elastomer (POE) open-cell foam material and a preparation method thereof, comprising the following components in percentage by mass: 60.0%-90.0% of a thermoplastic elastomer (POE) substrate, 5.0%-20.0% of a second component, 3.0%-10.0% of a fiber-type functional filler, 1.5%-3.0% of a compatibilizer, 0.2%-2.0% of a cross-linking agent, 0.2%-2.0% of a cell stabilizer, and 0.1%-3.0% of a composite foaming agent. It is prepared by continuous extrusion physical foaming, wherein the composite foaming agent is injected in stages during the extrusion process to achieve controllable foaming. The obtained foam is a high-performance foam with an open cell rate of ≥93%, a foaming ratio of 20-25 times, a uniform cell size (150-200 μm), an adsorption performance of ≥30 g / g, a compression rebound rate of ≥93%, and a shrinkage rate of ≤3%, which broadens the application of POE foam materials in the field of environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer material processing, and in particular to a thermoplastic elastomer (POE) open-cell foam material with ultra-high open porosity and adsorption performance and a preparation method thereof, wherein a twin-screw extruder connected in series with a static mixer is used to achieve continuous extrusion foaming. Background Art

[0002] Open-cell elastomeric foam is a polymer material with interconnected pores, combining the flexibility of elastomers with the lightweight properties of foam materials. It is widely used in automotive, construction, electronics, new energy, sound absorption, oil absorption, biomedicine, and other fields. For example, in terms of sound absorption, open-cell foam materials can effectively absorb sound wave energy and reduce noise pollution, and are often used as sound insulation materials in construction, automobiles, aircraft, and other fields. In the biomedical field, open-cell foam materials can be used to manufacture bioscaffolds and tissue engineering materials. Their porous structure facilitates cell attachment and growth, providing an excellent material foundation for regenerative medicine and tissue repair. In the field of environmental protection, open-cell foam materials also have good oil absorption properties and can be used to treat problems such as oil spills, which has important environmental significance. Among them, thermoplastic elastomer (POE) open-cell foam is particularly outstanding due to its unique performance advantages. With the continuous development of science and technology, the performance requirements for materials are also becoming increasingly stringent. However, the high density, poor stability, and high cost of POE materials limit their application in emerging fields. The introduction of a cellular structure into POE reduces the material's density and hardness while also enabling it to continuously develop towards higher performance and multifunctionality, such as thermal insulation, shock absorption, sound insulation, and oil absorption for environmental protection. Furthermore, the development of POE foam effectively reduces plastic consumption and increases product cost-effectiveness.

[0003] CN112341687A discloses a preparation process of a high-resilience, impact-resistant polyolefin foam material, but uses azodicarbonamide (AC) as a chemical foaming agent. The masterbatch is extruded by an extruder, irradiated and cross-linked, and foamed in a free-style manner to obtain a polyolefin foam material. Although the resulting open-cell polyolefin foam material has good resilience and impact resistance, the chemical foaming method is not environmentally friendly and the process is complicated. In addition, the patent does not describe its open-cell adsorption capacity. CN117624782B discloses an open-cell polymer foam and its preparation method. The raw material is a high-melting High-strength polypropylene and ethylene-octene copolymer elastomer (7:3) are melt-blended, and intermittent physical foaming is adopted as the foaming method; CN114395161B discloses a foamable thermoplastic polyurethane elastomer, its preparation method and application, wherein a foamable thermoplastic polyurethane elastomer is obtained by connecting a twin-screw extruder in series with a single-screw extruder, and foamed thermoplastic polyurethane elastomer beads are obtained by intermittent physical foaming, which are then foamed and welded in a mold using steam or microwave radiation to obtain a thermoplastic polyurethane foam product with excellent appearance, light weight, high resilience and high strength.

[0004] Currently, the main foaming methods for POE materials include chemical foaming, intermittent physical foaming, and continuous extrusion foaming. However, chemical foaming agents such as AC produce harmful gases during the foaming process, polluting the environment. They also complicate the process and increase costs, significantly impacting product quality stability. Intermittent physical foaming, which typically requires equipment such as autoclaves, has low production efficiency and is difficult to meet the needs of large-scale continuous production. In contrast, continuous extrusion physical foaming technology has attracted widespread attention as a means to effectively improve material properties.

[0005] Traditional POE foam materials have problems such as low open cell rate (<85%), insufficient compression rebound rate (<80%), weak adsorption performance (<30 g / g), and high shrinkage rate (>10%). In addition, conventional fillers (such as talcum powder) are difficult to support the foam structure and easily lead to collapse. Existing POE foam materials lack targeted design in open cell adsorption, compression rebound and other properties, making it difficult to meet more comprehensive application needs.

[0006] Based on this, the present invention proposes a method for preparing POE foam materials based on continuous extrusion physical foaming technology, which not only overcomes the shortcomings of traditional foaming methods, but also further improves the performance of POE foam materials through innovative means such as modification. It successfully develops a POE open-cell foam material with high open porosity and foaming ratio, uniform pore size, strong adsorption performance, high compression rebound rate and excellent anti-shrinkage performance, which provides a new solution to meet the needs of high-performance materials in different fields and is of great significance. Summary of the Invention

[0007] In order to overcome the above-mentioned technical defects, the purpose of the present invention is to provide a new thermoplastic elastomer POE open-cell foam material and a preparation method thereof. By optimizing the formula combination and foaming process, efficient foaming and multifunctional integration of the material are achieved. The material has a high open porosity and foaming ratio, strong adsorption performance, high compression rebound rate, low shrinkage rate, and the preparation method is simple and easy to control.

[0008] In order to solve the above problems, the present invention is implemented according to the following technical solutions:

[0009] A thermoplastic elastomer (POE) open-cell foam material comprises the following components in percentage by mass:

[0010] Thermoplastic elastomer POE substrate 60.0%-90.0%;

[0011] The second component is 5.0%-20.0%;

[0012] Fiber functional fillers 3.0%-10.0%;

[0013] Compatibilizer 1.5%-3.0%;

[0014] Cross-linking agent 0.2%-2.0%;

[0015] Cell stabilizer 0.2%-2.0%;

[0016] Composite foaming agent 0.1%-3.0%.

[0017] The material is prepared by continuous extrusion physical foaming based on the above components, wherein the composite foaming agent is injected in stages during the extrusion process. The material has ultra-high open porosity, adsorption performance and low shrinkage, with an open porosity of ≥93%, adsorption performance of ≥30g / g and shrinkage of ≤3%.

[0018] The thermoplastic elastomer POE substrate is an ethylene-octene copolymer with a melt index of 10-20 g / 10 min (190° C., 2.16 kg).

[0019] The second component includes one or more of ethylene-vinyl acetate copolymer (EVA), ethylene-ethyl acrylate copolymer (EEA), polybutadiene (PB), high-density polyethylene (HDPE), and polypropylene (PP), and has the characteristics of low viscosity and high melt index.

[0020] The fiber functional filler includes one or more of cellulose nanofiber (CNF), wood fiber, chopped carbon fiber, carbon fiber, and polyester fiber. The fiber diameter is 2-10 nm and the length is 0.5-5 μm. It has the functions of supporting foam cells, resisting shrinkage, and facilitating cell opening.

[0021] The compatibilizer is one or a mixture of maleic anhydride grafted thermoplastic elastomer POE-g-MAH, ethylene-vinyl acetate copolymer, styrene-poly(ethylene-butylene)-polystyrene block copolymer, chlorinated polyethylene, and epoxy natural rubber. The main function of the compatibilizer is to increase the compatibility of the two polymers, increase the adhesion between the two polymers, and form a stable structure.

[0022] The crosslinking agent is one or a mixture of dicumyl peroxide (DCP), dibenzoyl peroxide (BPO), dilauroyl peroxide (LPO), benzoyl peroxide (BPO), and di-tert-butyl peroxide (DTBP). The main function of the crosslinking agent is to connect the molecular chains of POE and the second component together to form a three-dimensional network structure, thereby improving the mechanical properties and dimensional stability of the material.

[0023] The cell stabilizer is one or a mixture of zinc stearate, liquid paraffin, polybutadiene, dimethyl polysiloxane, and sulfonated fatty alcohol. The main function of the cell stabilizer is to increase the strength of the cell wall, prevent the cell wall from breaking, and stabilize the cells.

[0024] The composite foaming agent is air and supercritical gas, wherein the supercritical gas is one or more of supercritical nitrogen and supercritical carbon dioxide.

[0025] In order to solve the above problems, the second object of the present invention is to provide a method for preparing a thermoplastic elastomer (POE) open-cell foam material, which is simple to operate and easy to manufacture.

[0026] The preparation method of the thermoplastic elastomer POE open-cell foam material of the present invention is implemented according to the following technical scheme, including:

[0027] S1. Raw material pretreatment: Prepare the following components in mass percentage, including 60.0%-90.0% of thermoplastic elastomer POE base material, 5.0%-20.0% of the second component, 3.0%-10.0% of the functional filler, 1.5%-3.0% of the compatibilizer, 0.2%-2.0% of the cross-linking agent, and 0.2%-2.0% of the cell stabilizer. Mix them evenly after drying. Usually, the raw materials can be placed in a vacuum dryer at 80°C for 6 hours, and then added to a high-speed mixer and mixed for 5-20 minutes to ensure that the components are fully mixed;

[0028] S2. Melt blending: adding the obtained uniformly mixed raw materials into an extruder, with the temperature of each section of the extruder being 160-220°C, the screw speed being 50-400 r / min, the blending time being 10-20 min, and the extrusion pressure being 5-20 MPa;

[0029] S3. Extrusion foaming: A static mixer is connected in series at the extruder outlet, and 0.1%-3% of a composite foaming agent is injected into the extruder. After sufficient mixing, the POE open-cell foam material is obtained by extrusion foaming. The supercritical gas in the composite foaming agent is injected into the compression section of the extruder, and the air is injected into the homogenization section of the extruder.

[0030] Furthermore, during the extrusion foaming process, the extruder is a twin-screw extruder connected in series with a static mixer. The twin-screw extruder has unique screw and threaded elements. The static mixer is installed between the extruder and the die to further divert and mix the melt, fully transfer heat, and reduce the temperature, which is conducive to stabilizing the extrusion pressure and flow rate, making the extrusion process more stable, thereby improving production efficiency and product quality. The temperature of the static mixer is controlled at 70-110°C, the pressure is controlled at 5-15 MPa, and the processing temperature zones of the twin-screw extruder are set to 160-170°C for zone one, 170-180°C for zone two, and 180-190°C for zone three. The die head temperature is 190-220°C.

[0031] Furthermore, through component regulation and process optimization, the prepared POE open-cell foam material achieved exceptionally excellent performance, with an open porosity ≥93%, a foaming ratio of 20-25 times, a uniform pore size (150~200 μm), an adsorption performance ≥30 g / g, a compression rebound rate ≥93%, and a shrinkage rate ≤3%.

[0032] The present invention achieves multiple advantages such as high open-pore adsorption, high compression rebound rate and anti-shrinkage by regulating the component ratio and optimizing the foaming process under continuous extrusion physical foaming conditions. It effectively reduces the shrinkage of the material during the foaming process, improves the dimensional stability of the product, effectively improves the elasticity and recovery performance of the material, enables it to quickly return to its original shape after being subjected to external force, enhances the durability of the material, and effectively improves the open-pore adsorption performance, so that the POE foam material can be better applied to oil pollution adsorption, river / ocean pollution control, heavy metal wastewater treatment, air purification and other fields, and has high practical value.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) Component innovation: introducing a second component with low viscosity and high melt index into the POE molten matrix can improve the elasticity and processing performance of the material, and at the same time form good compatibility with the POE substrate, which is conducive to the foaming process; fiber-type functional fillers form a three-dimensional network structure by combining with POE, which can not only enhance the mechanical properties of the material, but also support the bubbles, resist shrinkage and facilitate the formation of an open-cell structure; using composite foaming agents such as supercritical nitrogen and / or supercritical carbon dioxide-air for synergistic foaming, supercritical nitrogen and / or supercritical carbon dioxide are injected into the compression section of the extruder to play a protective role and prevent high-temperature oxidative degradation, and air is injected into the homogenization section of the extruder to play an anti-shrinkage role, induce open cells, and form a uniform open-cell structure.

[0035] (2) The thermoplastic elastomer POE open-cell foam material described in the present invention has a high open-pore ratio and foaming ratio, strong adsorption performance and excellent oil absorption effect on various oils, high compression rebound rate, good anti-shrinkage performance, and is reusable.

[0036] (3) The present invention provides a method for preparing a thermoplastic elastomer POE open-cell foam material, which is simple to operate and easy to manufacture. The POE open-cell foam material obtained by melt blending and extrusion foaming in an extruder combined with a twin-screw series static mixer not only maintains the advantages of excellent toughness and good processability, but also uses air as a physical foaming agent, which is in line with the current social development needs of advocating a green and low-carbon economy, reduces the POE foaming cost, is conducive to the development of thermoplastic elastomer POE open-cell foam, broadens its application range, and meets the current social demand for high-performance materials. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention and are not intended to limit the present invention.

[0038] All test instruments and reagents are commercially available and can be purchased through commercial channels. The specific sources of the chemical agents used in the Examples and Comparative Examples of the present invention are:

[0039] POE: Brand 8440, manufactured by Dow Chemical, USA, melt flow rate is 1.6 g / 10 min.

[0040] EVA: brand UL01833, manufacturer is Lianhong New Materials Technology Co., Ltd., melt flow rate is 18g / 10 min, VA content is 33 wt%.

[0041] CNF: Model J6426CP, diameter between 5 and 10 nm, length between 0.5 and 1 nm.

[0042] POE-g-MAH: Brand N216, manufactured by Dow Chemical, USA, with a melt index of 1.25 g / 10 min.

[0043] DCP: Model BC-FF, manufactured by Akzo Nobel, melting point 39.5 °C.

[0044] Zinc stearate: The manufacturer is Zanyu Technology Group Co., Ltd., the zinc content is 10.3~11.3%, and the melting point is 120℃.

[0045] Supercritical nitrogen: The manufacturer is Beijing Oriental Medical Gas Co., Ltd., with a purity of 99.99%.

[0046] The preparation processes of the thermoplastic elastomer POE open-cell foam materials of the comparative examples and the examples are as follows:

[0047] S1. Raw material pretreatment: Prepare the corresponding amounts of thermoplastic elastomer POE substrate, second component, functional filler, compatibilizer, crosslinking agent, and cell stabilizer in the components of Comparative Examples 1-7, Comparative Example 9, and Examples 8 and 10-12 in Table 1, and then place them in a vacuum dryer at 80°C for 6 hours, and then add them to a high-speed mixer and mix for 15 minutes to ensure that all components are fully mixed;

[0048] S2. Melt blending: The obtained uniformly mixed raw materials were added to a twin-screw extruder. The processing temperature zones were set to 165°C for zone 1, 175°C for zone 2, and 185°C for zone 3. The die temperature was 190°C, the screw speed was 300 r / min, the blending time was 15 min, and the extrusion pressure was 15 MPa.

[0049] S3. Extrusion foaming: Supercritical nitrogen-air synergistic foaming is adopted. Supercritical nitrogen is injected into the compression section of the extruder at an injection rate of 5 MPa. Air is injected into the homogenization section of the extruder at an injection rate of 10 MPa. A static mixer is connected in series at the outlet of the twin-screw extruder. The pressure is controlled at 12 MPa. After sufficient mixing, the POE open-cell foam material is obtained by extrusion foaming.

[0050] Table 1 Components of Comparative Examples 1-7, Comparative Example 9 and Examples 8 and Examples 10-12

[0051]

[0052] Effect test

[0053] 1) Testing the open porosity of foam using an open / closed porosity tester: This method uses the gas displacement method to measure the open / closed porosity of rigid foam, in compliance with GB / T 10799 and ASTM D2856 standards. The specific steps are as follows: Before analyzing the sample, perform a volume calibration on the instrument before beginning the test. Cut the sample into two cubes with a side length of 25 mm. Use a balance to accurately read the sample mass and measure the geometric volume V of the two cubes. g Place the two cubes in the sample cell of the open and closed porosity tester, close the chamber cover, and start the test. The instrument will measure the gas displacement volume V. p1 After the test, open the sample chamber cover, take out the two cubes, and cut them three times along lines parallel to the sides of the cubes to obtain 16 small cubes. The exposed surface and the number of openings caused by cutting will be doubled. Place the 16 cut small cubes into the sample cell, close the chamber cover, and continue the test. The instrument will measure their volume V. p2. Test at least 5 samples.

[0054] Porosity calculation: The volume of the open pores in the porous material is V oc The volume of the cut pores on the original surface of the sample is V cc , then V p1 and V p2 The relationships are as follows:

[0055] V p1 =V g -V oc -V cc (1)

[0056] V p2 =Vg-V oc -2V cc (2)

[0057] Then V oc =V g -2V p1 +V p2 (3)

[0058] Opening rate C o =V oc / V g *100% (4)

[0059] 2) Use a density balance to test the foam density and calculate the expansion ratio in accordance with GB / T 6343-2009. Use a scanning electron microscope combined with image analysis software Image-Pro Plus to calculate the average cell size:

[0060] Specifications of the sample: The shape of the sample should be convenient for volume calculation. The sample of the present invention is a cubic sample with a side length of 25 mm. At least 5 samples are tested.

[0061] Specific steps of performance test: After the test sample material is produced, place it in a dry environment for at least 16 hours before preparing the sample. Use a density balance to weigh the sample mass (m), and calculate the volume (V) of the sample through geometric dimension measurement. The foam density ρ f = m / V, expansion ratio φ = ρ / ρ f ρ represents the density of the unfoamed material. Foam samples were placed in liquid nitrogen for at least 2 hours before being quenched and fractured. The quenched surface was then subjected to a gold-spraying treatment and placed under a scanning electron microscope to capture appropriate electron micrographs (containing ≥100 cells) to accurately measure cell size and minimize measurement error. The average cell size was then calculated using the image analysis software Image-Pro Plus.

[0062] Calculation of average cell size:

[0063]

[0064] Where d i is the diameter of each cell, and n is the number of cells in the measurement area.

[0065] 3) Use an electronic balance to measure the mass change of the foam before and after adsorption of silicone oil and calculate the adsorption amount:

[0066] Specifications of the sample: cube with a side length of 25 mm, at least 5 samples are tested in each group.

[0067] The specific steps of the performance test are as follows: dry the sample to constant weight and weigh the sample mass (m1). Then immerse the sample in silicone oil for 24 hours to ensure sufficient adsorption. Remove the sample, absorb the excess silicone oil on the surface with filter paper, and weigh the mass of the sample after adsorption (m2).

[0068] The adsorption amount calculation formula is: adsorption amount = (m2−m1) / m1×100%.

[0069] 4) Use a universal testing machine to test the compression rebound rate of the foam:

[0070] Specifications of the sample: cube with a side length of 10 mm, at least 5 samples are tested in each group.

[0071] The specific steps of the performance test are as follows: set the experimental program of the universal testing machine, compress to 50% strain, hold for 30 seconds, then release the pressure to the initial position, and measure the height h1 of the sample recovered 30 minutes after pressure release.

[0072] Compression rebound rate R=h1 / h0×100%, where h0 is the original height of the sample.

[0073] 5) Calculate the shrinkage of foam by the expansion ratio:

[0074] The specific steps of the performance test are as follows: After foaming, the foam sample is quickly cut into a cube with a side length of 25 mm, and then the density of the foam is measured with a density balance to obtain its foaming ratio φ0. After the sample is placed in a laboratory environment for 72 hours, the density test is performed again to obtain its foaming ratio φ0. t At least 5 samples were tested in each group.

[0075] Shrinkage S (%) = (φ0-φ t ) / φ0×100%.

[0076] Table 2 shows the comparison of the test results of the thermoplastic elastomer POE open-cell foam materials prepared in the comparative example and the example.

[0077] Table 2 Test results of foamed products obtained in comparative examples and examples

[0078]

[0079] The static mixer, installed between the extruder and the die, further divides and mixes the melt, effectively transferring heat and lowering the temperature. This helps stabilize extrusion pressure and flow rate, resulting in uniform cell size and distribution in the POE open-cell foam, thereby improving the material's open-cell ratio and compression rebound properties. For example, in Comparative Example 1, which does not use a static mixer, the open-cell ratio is only 56% and the compression rebound is only 55%. In contrast, in Comparative Example 2, which uses a static mixer, both the open-cell ratio and compression rebound are improved.

[0080] Functional fillers form a three-dimensional network with the POE substrate, supporting the cells and resisting shrinkage, which facilitates the formation of an open-pore structure and improves adsorption performance. For example, comparing Comparative Example 5 with Comparative Example 6, the addition of the functional filler CNF in Comparative Example 6 increases the open-pore ratio and reduces the shrinkage. Comparing Example 8 with Example 11, it can be seen that increasing the amount of functional filler further improves performance. Example 11 improves the open-pore ratio, adsorption performance, and compression rebound, while the shrinkage of the system is only 2.4%.

[0081] The synergistic use of supercritical nitrogen and air significantly impacts porosity and shrinkage. Supercritical nitrogen is injected into the compression section of the extruder to protect against high-temperature oxidative degradation, while air is injected into the homogenization section to counteract shrinkage and induce porosity. Comparing Example 8 with Comparative Example 9, which uses only supercritical nitrogen as a foaming agent, exhibits a porosity of only 81% and a shrinkage of 3.3%. In contrast, Example 8, which uses a composite foaming agent, exhibits a porosity of 93% and a shrinkage of only 2.8%.

[0082] Comparative Example 3 reveals that the addition of the second component has little effect on the open cell ratio, foaming, adsorption performance, compression rebound, and shrinkage. The addition of a functional filler in Comparative Example 4 significantly improves the open cell ratio, foaming, adsorption performance, and compression rebound, while reducing shrinkage. In contrast, Comparative Example 6, which adds both the second component and the functional filler, yields an even more superior, shrinkage-resistant foam with high open cell ratio, high foaming ratio, high adsorption performance, and high compression rebound. This demonstrates a synergistic effect between the second component and the functional filler, enhancing open cell adsorption, foaming, high compression rebound, and shrinkage resistance. Furthermore, a comparison of Examples 8, 10, and 11 reveals that appropriately increasing the amount of the second component and the functional filler significantly improves the performance of the POE foam. Example 12, in which both the second component and the functional filler are added, achieves an open cell ratio of 98%, a foaming ratio of 20 times, uniform cell size (150-200 μm), an adsorption performance of 40 g / g, a compression rebound of 96%, and a shrinkage of 2.1%, representing exceptionally excellent performance.

[0083] The above description is merely a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Therefore, any modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention shall still fall within the scope of the technical solution of the present invention.

Claims

1. A thermoplastic elastomer (POE) open-cell foam material, characterized in that: Contains the following components in percentage by mass: Thermoplastic elastomer POE substrate 60.0%-90.0%; The second component is 5.0%-20.0%; Fiber functional fillers 3.0%-10.0%; Compatibilizer 1.5%-3.0%; Cross-linking agent 0.2%-2.0%; Cell stabilizer 0.2%-2.0%; Composite foaming agent 0.1%-3.0%; The second component includes one or more of ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, polybutadiene, high-density polyethylene, and polypropylene; the fiber-based functional filler includes one or more of cellulose nanofiber, wood fiber, carbon fiber, and polyester fiber; the composite foaming agent is air and one or more supercritical gases as a foaming agent; the material is prepared by continuous extrusion physical foaming, and its preparation method includes: S1. Raw material pretreatment: prepare the thermoplastic elastomer POE substrate, the second component, the fiber functional filler, the compatibilizer, the crosslinking agent, and the cell stabilizer according to the mass percentage, and mix them thoroughly after drying; S2. Melt blending: adding the obtained uniformly mixed raw materials into an extruder, with the temperature of each section of the extruder being 160-220°C, the screw speed being 50-400 r / min, the blending time being 10-20 min, and the extrusion pressure being 5-20 MPa; S3. Extrusion foaming: The extruder outlet is connected in series with a static mixer, and the composite foaming agent is injected into the extruder. After sufficient mixing, it is extruded and foamed to obtain a thermoplastic elastomer POE open-cell foam material, wherein the supercritical gas in the composite foaming agent is injected in the compression section of the extruder, and the air is injected in the homogenization section of the extruder.

2. The thermoplastic elastomer POE open-cell foam material according to claim 1, characterized in that: The material has an open porosity of ≥93%, an adsorption performance of ≥30g / g, and a shrinkage rate of ≤3%.

3. The thermoplastic elastomer POE open-cell foam material according to claim 1, characterized in that: The POE substrate is ethylene-octene copolymer, with a melt index of 10-20 g / 10 min, 190° C., and 2.16 kg.

4. The thermoplastic elastomer POE open-cell foam material according to claim 1, characterized in that: The fiber functional filler has a fiber diameter of 2-10 nm and a length of 0.5-5 μm.

5. The thermoplastic elastomer POE open-cell foam material according to claim 1, characterized in that: The compatibilizer is one or a mixture of maleic anhydride grafted thermoplastic elastomer POE-g-MAH, ethylene-vinyl acetate copolymer, styrene-poly(ethylene-butylene)-polystyrene block copolymer, chlorinated polyethylene, and epoxy natural rubber.

6. The thermoplastic elastomer POE open-cell foam material according to claim 1, characterized in that: The cross-linking agent is one or a mixture of dicumyl peroxide, dibenzoyl peroxide, dilauroyl peroxide, benzoyl peroxide, and di-tert-butyl peroxide.

7. The thermoplastic elastomer POE open-cell foam material according to claim 1, characterized in that: The cell stabilizer is one or a mixture of zinc stearate, liquid paraffin, polybutadiene, dimethyl polysiloxane, and sulfonated fatty alcohol.

8. The thermoplastic elastomer POE open-cell foam material according to claim 1, characterized in that: The supercritical gas in the composite foaming agent is supercritical nitrogen or supercritical carbon dioxide.

9. A method for preparing a thermoplastic elastomer (POE) open-cell foam material according to any one of claims 1 to 8, characterized in that: include: S1. Raw material pretreatment: prepare the following components by mass percentage: 60.0%-90.0% of thermoplastic elastomer POE base material, 5.0%-20.0% of the second component, 3.0%-10.0% of fiber functional filler, 1.5%-3.0% of compatibilizer, 0.2%-2.0% of cross-linking agent, 0.2%-2.0% of cell stabilizer, and mix thoroughly after drying; S2. Melt blending: adding the obtained uniformly mixed raw materials into an extruder, with the temperature of each section of the extruder being 160-220°C, the screw speed being 50-400 r / min, the blending time being 10-20 min, and the extrusion pressure being 5-20 MPa; S3. Extrusion foaming: A static mixer is connected in series at the extruder outlet, and 0.1%-3% of a composite foaming agent is injected into the extruder. After sufficient mixing, the extrusion foaming molding is performed to obtain a thermoplastic elastomer POE open-cell foam material. The supercritical gas in the composite foaming agent is injected into the compression section of the extruder, and the air is injected into the homogenization section of the extruder.

10. The method for preparing the thermoplastic elastomer POE open-cell foam material according to claim 9, characterized in that: The extruder is a twin-screw extruder, and a static mixer is connected in series at its outlet. The static mixer is installed between the extruder and the die. The temperature of the static mixer is controlled at 70-110°C, and the pressure is controlled at 5-15 MPa. The processing temperature zones of the twin-screw extruder are set to 160-170°C for zone one, 170-180°C for zone two, and 180-190°C for zone three. The die head temperature is 190-220°C.

Citation Information

Patent Citations

  • High-resilience and impact-resistant polyolefin foam material and preparation process thereof

    CN112341687A

  • A foamable thermoplastic polyurethane elastomer, its preparation method and application

    CN114395161B

  • Open-cell polymer foam and preparation method thereof

    CN117624782B

  • Method of producing compostable or biobased foams

    CA2778641A1

  • Wear-resistant rubber foaming sports shoe material and preparation method thereof

    CN112795062A